Satisfactory function 12 years after triscaphoid arthrodesis for chronic scapholunate ligament injury. Issue 4 (3rd July 2020) - Reigstad, Ole; Grimsgaard, Christian; Holm-Glad, Trygve; Korslund, Johanne; Thorkildsen, Rasmus D.; Røkkum, Magne
Abstract: Scapholunate ligament (SLL) injury represents a hazard to the wrist and the treatment of these injuries has been the focus of much debate. We performed a long-term follow (>10 years) of triscaphoid arthrodesis for symptomatic chronic SLL injuries in 10 (8 men) patients 37 (22–49) years of age. All arthrodesis healed. One patient was converted to total wrist arthrodesis during the follow-up period, and three had minor additional surgeries. At final follow-up, the patients had reduced active range of motion (AROM, 55%) and grip strength (85%) compared to the opposite side, but reported low Quick Disability of Arm, Shoulder and Hand (QDASH) (11), Patient-Rated Wrist and Hand Evaluation (PRWHE) (25) and visual analog scale (VAS) pain scores (0 and 10 at rest and activity). Radiographs found minimal degenerative changes in four patients, while CT scans demonstrated changes in seven patients, in three of these scaphoid was subluxed on the rim of the radius. The patients working prior to surgery were working at follow-up. A triscaphoid arthrodesis for SLL renders a functional wrist function in most patients for many years and has postponed more extensive surgery like total wrist arthrodesis or wrist arthroplasty. The patients are still young, and the degenerative changes seen especially on CT scans warrants attention.